Построение архитектуры интеллектуальной системы управления адаптивного головного света автомобиля на основе интернет-технологий - Никонов, О. Я.; Баранова, В. О. (НТУ "ХПИ", 2015)
Современные высокотехнологичные фары автомобилей существенно повышают уровень дорожной безопасности. Адаптивная система переднего освещения становится все более популярной сегодня. При моделировании системы управления автовыравнивания очень важно обеспечить ее функциональность и сравнить реальный выход системы. В данной статье рассмотрены составляющие компоненты интеллектуальной системы переднего освещения автомобиля и разработана архитектура системы на основе интернет-технологий.

The highest fatal traffic accident rate occurs on curved roads at nighttime. In most cases, the late recognition of objects in the traffic zone plays a key role. These facts point to the importance of the role of automobile forward-lighting systems. In order to provide enhanced nighttime safety measures, this work aims to design and build a prototype of steerable headlights by adapting a conventional static headlamp with a very close eye on cost and reliability. Components that are easily available in the market and suitable for developing a steerable headlight system were tested. Different kinds of tests were done on critical parts of the system in order to determine its accuracy, its response time, and the system impact. Finally, the results acquired from these various tests will be discussed. Any findings and changes that should be made are discussed and may be useful for future development. Modern high-tech car headlights greatly increase the level of road safety. Adaptive front-lighting system is becoming more and more popular today. Beginning in the 2000s, there was a resurgence in interest in the idea of moving or optimizing the headlight beam in response not only to vehicular steering and suspension dynamics, but also to ambient weather and visibility conditions, vehicle speed, and road curvature and contour. In the simulation control system Auto-Align is very important to ensure its functionality and to compare the actual output of the system. This article describes the component parts of the intellectual front-lighting systems of the car, as well as the principle of the functional circuit.
Construction аrchitecture of intelligent control system of adaptive headlight car based on Internet technologies
Keywords: фары; дорога; система переднего освещения; видимость; intelligent control system; headlights; vehicle; road; adaptive front-lighting system